The “beautiful” concept in english - Tursunoy Yandashova (Indonesian Journal of Innovation Studies, 2019)
This page describes the significance of the concept of computing, as well as the development of uzbek culture in the community. in particular, the concept of "beauty" is strongly influenced by the author's views on the interconnectedness of the education. It conludes with the major points of the research.